The Deep Inferior Epigastric Perforator (DIEP) Flaps in Breast Reconstruction After Mastectomy - Parikesit, Dyandra; Ashton, Mark (Jurnal Plastik Rekonstruksi, 2012)
Background: The continuing advances in breast reconstruction surgery allows for high expectation of excellent outcomes and long-term aesthetic appearance. Transverse rectus abdominis muscle (TRAM) flap has been the flap of choice in breast reconstructions for decades, however it sacrifices muscle and causes donor site complication. Deep inferior epigastric perforator (DIEP) flap is now the preferred flap for microsurgical breast reconstruction, because it holds some advantages over TRAM. This study aim to review, summarize, and discuss the current knowledge of DIEP flap in breast reconstruction.Method: Literature research conducted through Pubmed, Medline, and SCOPUS databases for published articles up to the year 2009. A total of 808 articles were found, and 60 articles reviewed.Result: Women with thick subcutaneous fat and skin on the lower abdomen are the most appropriate candidates for autologous breast reconstruction. Patients might be given oral analgesics instead of intravenous, because DIEP results in less postoperative pain than TRAM. Patients are commonly discharged on the 6–7th day post operation after DIEP flaps. In spite of several reports that DIEP flap has low complication rates, necrosis is the most common and often leads to poor cosmetic outcome.Conclusion: DIEP flap essentially combines all the advantages of TRAM flap without most of its disadvantages. Some complications may occur in smaller percentage. Although DIEP flap has a high patient satisfaction score, it does not mean that it is definitely superior to other methods of autologous breast reconstruction.